MODEL OF WORK OF GRANT FUND - T. Gataullin; S. Nikolotova; L. Goncharov (Вестник университета, 2016)
Authors considered a question of grant science funding very actual today, the short analysis of the situation which developed in this direction in Russia is carried out, the model is offered and some features of work of grant fund are considered. The graphic illustration of the offered mathematical model is given.